The Effect of News on Twitter Related to Sexual Harassment of Women on The Level of Anxiety of Female Students - Feni Lestari; Nur Mala Pusphita Sari; Zainal Abidin; Nafida Hetty Marhaeni (Lembaga Junal dan Publikasi, Universitas Muhammadiyah Buton, 2022)
Twitter is one of the social media that is widely used by the public to find information. One of the news that is often highlighted on this platform is news related to sexual harassment. The purpose of this study was to determine the influence and relationship of reports of sexual harassment spread through Twitter social media on the anxiety level of female students. This research uses quantitative research methods with shortor explanatory methods. The population in this study was female students of the Communication Science Study Program, Mercu Buana University Yogyakarta class of 2021 as many as 126 female students. The data collection technique used is a questionnaire on the influence of media use and a questionnaire for meeting information needs. The data obtained were analyzed using SPSS Version 20 software. The results showed that there was no relationship or influence of sexual harassment reports spread through Twitter social media on female students' anxiety.